Promotion of oral health and Atraumatic Restorative Treatment from the perspective of pre-school, educators and parents (Research, Society and Development, 2021)
Recommendations for health promotion practices in collective environments and conservative restorative treatments represent strategies for the prevention of oral diseases from childhood. Objective: To investigate the perception of preschoolers, educators and parents regarding the recommendations received from dental students for the prevention of caries disease and the use of Atraumatic Restorative Treatment (ART) in a Child Education Center. This is an exploratory descriptive observational study with a qualitative approach. Semi-structured interviews were carried out with 18 children from 4 to 5 years of age, educational activities, oral health care, supervised brushing and Atraumatic Restorative Treatment. About 18 educators and 37 parents answered a form with open and closed questions about promoting oral health at school, the impact of educational-preventive activities, caring for primary teeth and the use of Atraumatic Restorative Treatment. The children's interviews were transcribed, coded and analyzed by Discourse Analysis, as well as the forms of educators and parents. Results: The acceptance of children regarding the presence of a dentist and use of ART was 89%. About 83% of them associated poor hygiene and the intake of sugary foods as triggers of tooth decay. As for educators, 44% studied oral health only in graduate school, but they agreed on the importance of the topic in the curriculum, for 60% caries was a disease, and 50% observed toothache in children. Already 67.5% of parents did not notice caries in their children, and only 4 reported pain, however all agreed on the beneficial effects of educational/preventive activities and the use of ART in children. Conclusions: Preschool children showed understanding about the concept of dental caries and ways of prevention, felt encouraged to self-care, and accepted ART. Educators and parents observed that actions to promote oral health and ART in the school environment promoted autonomy and empowerment for children, generating changes in their behavior.